Algoritma Brute Force Pada Aplikasi Kritik dan Saran Mahasiswa Berbasis Digital - Riyan Wahyu Nur Hidayah; Fauziah Fauziah; Albaar Rubhasy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The Criticism and Suggestion application is an android-based application intended to provide input and criticism to related agencies, in planning to build this application an algorithm method is needed to match strings. This research was made to make it easier for students to express their opinions. The method used is the brute force algorithm method, this method is used to search for terms in the application made, the brute force algorithm is an algorithm that has a straight nature. The brute force algorithm is a very complicated algorithm, the reason is that with this method to solve problems using a straight forward technique, it takes several inputs and valid considerations, so that you often get problem solving decisions that directly refer to the brute force algorithm or lead to the desired results. . The results of the unit area analysis are to make it easier for users or users to generate criticism and input for their fields and therefore the results of the brute force algorithm program will display the results of thoughts, criticisms and inputs for that field.